Therapeutic Perspectives of Adenosine Deaminase Inhibition in Cardiovascular Diseases - Kutryb-Zajac, Barbara (Molecules, 2020)
Adenosine deaminase (ADA) is an enzyme of purine metabolism that irreversibly converts adenosine to inosine or 2′deoxyadenosine to 2′deoxyinosine. ADA is active both inside the cell and on the cell surface where it was found to interact with membrane proteins, such as CD26 and adenosine receptors, forming ecto-ADA (eADA). In addition to adenosine uptake, the activity of eADA is an essential mechanism that terminates adenosine signaling. This is particularly important in cardiovascular system, where adenosine protects against endothelial dysfunction, vascular inflammation, or thrombosis. Besides enzymatic function, ADA protein mediates cell-to-cell interactions involved in lymphocyte co-stimulation or endothelial activation. Furthermore, alteration in ADA activity was demonstrated in many cardiovascular pathologies such as atherosclerosis, myocardial ischemia-reperfusion injury, hypertension, thrombosis, or diabetes. Modulation of ADA activity could be an important therapeutic target. This work provides a systematic review of ADA activity and anchoring inhibitors as well as summarizes the perspectives of their therapeutic use in cardiovascular pathologies associated with increased activity of ADA.